Interleukin-6: a molecule with complex biological impact in cancer - Lacina, Lukáš; Brábek, Jan; Král, Vladimír; Kodet, Ondřej; Smetana, Karel (Histology and histopathology, 2019)
Interleukin-6 is a multifaceted cytokine, usually reported as a pro-inflammatory molecule. However, certain anti-inflammatory activities were also attributed to IL-6. The levels of IL-6 in serum as well as in other biological fluids are elevated in an age-dependent manner. Notably, it is consistently reported also as a key feature of the senescence-associated secretory phenotype. In the elderly, this cytokine participates in the initiation of catabolism resulting in, e.g. sarcopenia. It can cross the blood-brain barrier, and so it is in causal association with, e.g. depression, bipolar disorder, schizophrenia, and anorexia. In the cancer patient, IL-6 is produced by cancer and stromal cells and actively participates in their crosstalk. IL-6 supports tumour growth and metastasising in terminal patients, and it significantly engages in cancer cachexia (including anorexia) and depression associated with malignancy. The pharmacological treatment impairing IL-6 signalling represents a potential mechanism of anti-tumour therapy targeting cancer growth, metastatic spread, metabolic deterioration and terminal cachexia in patients.
Keywords: interleukin-6; Animals; nádory; lidé; Neoplasms; Humans; Interleukin-6; zvířata